A geoarchaeological study of the construction of the Laona tumulus at Palaepaphos, Cyprus. Issue 4 (25th February 2021) - Gkouma, Myrsini; Karkanas, Panagiotis; Iacovou, Maria
Abstract: The tumulus of Palaepaphos‐Laona is a monumental earthwork. Its size makes it unique in the landscape of ancient Cyprus, where even smaller burial mounds are extremely rare. It is characterized by a composite s616sequence and a wide range of carefully arranged construction materials. To reconstruct the building process, we employed a geoarchaeological approach, including a high‐resolution microstratigraphic analysis. The study reveals a careful selection of construction materials and variability in the construction methods, reflecting a long tradition of building skills and empirical knowledge regarding the materials' engineering properties. It is evident that the tumulus of Laona was not a product of earth accumulation but an accomplished architectural structure. Several building stages were recorded, which along with repairs and intervals of exposure of the sediments, they represent temporal cycles of different nature and magnitude. As the height of the structure gradually increased, the tumulus became an imposing physical mark that gave the landscape a new meaning. Nevertheless, the memory of the ancestral testimony it was meant to convey to future generations was lost.